Exploring the Dimensions of Assurance, Empathy, and Evidence in Improving Service Quality and Customer Satisfaction: A Service Dominant Logic Theory Perspective - Bahktiar Tijjang (Universitas Dharma Wacana, 2022)
This research discusses the importance of service quality in creating a positive and satisfying customer experience. This research focuses on three key dimensions of service quality, namely assurance, empathy, and evidence, and how these dimensions can improve customer satisfaction. The research method used in this research is a literature study. The literature study was conducted by analyzing various sources of information related to service quality, including academic journals, books, and online articles.The results show that the three key dimensions of service quality - assurance, empathy, and evidence - are critical in creating a positive and satisfying customer experience. Assurance refers to the customer's trust and confidence in the company's ability to provide good service. Empathy refers to the company's ability to understand and respond to customers' needs and wants. Evidence refers to the physical or logical evidence that demonstrates the quality of service provided by the company.